The Effect of Learning Discipline on Learning Achievement of Class X Students in Vocational High School 5 Padang - Silvia Marti Veri; Nizwardi Jalinus; Hasan Maksum; Indah Permata Edi; Yumn Jamilah (International Journal of Educational Dynamics, 2020)
The research objective is to analyze the discipline of learning on learning achievement at Vocational High School 5 Padang class X. This study uses a correlational quantitative research type. Based on the research results obtained that there is a positive and significant relationship of learning discipline to the learning achievement of students of class X in Vocational High School 5 Padang of 11.97%.